Update on Management of Postoperative Atrial Fibrillation After Cardiac Surgery - Ronsoni,Rafael de March (2020)
Abstract Postoperative atrial fibrillation (POAF) after cardiac surgery remarkably remains the most prevalent event in perioperative cardiac surgery, having great clinical and economic implications. The purpose of this study is to present recommendations based on international evidence and adapted to our clinical practice for the perioperative management of POAF. This update is based on the latest current literature derived from articles and guidelines regarding atrial fibrillation.